The cleaving - McKenna, Juliet E. (Angry Robot, 2023)
"The Cleaving is an Arthurian retelling that follows the tangled stories of four women: Nimue, Ygraine, Morgana, and Guinevere, as they fight to control their own destinies amid the wars and rivalries that will determine the destiny of Britain."--